Distance Elasticity of Tourism Demand - BĘBEN, Robert; KRAUS, Zuzanna; PÓŁBRAT, Izabela (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
Understanding the behaviours of potential customers is crucial for effective management. Distance to destination and travel time are among the most important variables which influence customers' behaviours. The authors focused on the relation between the potential level of tourist demand and the distance to be travelled by tourists. The subject of the analysis presented in the paper shows the measurement of distance demand elasticity with selected variables that influence the tendency to stay far from an everyday environment for leisure time travels. The authors created a method called Distance Elasticity Meter (DEM), which allows to analyse a range of optimal travel times for different target groups. The results can be used to estimate the potential demand of a specific destination and for segmentation analysis. DEM enables the determination of a potential target market in conjunction with the communication access of certain destinations, but it can also have other applications.